HUBUNGAN CITRA TUBUH (BODY IMAGE) DENGAN KECEMASAN SOSIAL PADA REMAJA PEREMPUAN DI SMAN 1 PADALARANG - Fahiza Fauziah Azzahra; Roswendi, Achmad; Noch Bolla , Ibrahim (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background: Services that are not in accordance with patient expectations will lead to customer complaints, this is supported by the data on patient complaints at the Lubuk Besar Health Center in 2020 in 1 patient complaint a lot is found in the health center service by 66.67%, against health center facilities by 13.33%, friendliness of health center staff 13.33%, while the lowest patient complaints are found in the availability of drugs and the location of the health center posyandu by 6.6.7%. So that in providing services must be excellent, excellent service consists of 6 components, namely, attitude, ability, appearance, attention, action and responsibility. Good service can lead to patient satisfaction. Objective: This study aims to determine the relationship between excellent service and patient satisfaction based on patient perceptions at the Melong Tengah Health Center using the SERVQUAL method. Method: The design used is an analytic survey with a cross sectional approach. The sample size was 93 people using purposive sampling technique with inclusion and exclusion criteria. Data collection using a questionnaire with a Likert scale. Data analysis was carried out, namely univariate and bivariate (Chi-Square).. Results: Based on the results of univariate analysis, it can be seen that 51 people (54.8%) felt the service was not good and 51 people (54.8%) felt less satisfied. The Chi-Square test results show that there is a relationship between excellent service and patient satisfaction with a p value of 0.00 <0.05.. Conclusion: that there is a relationship between excellent service and patient satisfaction. Suggestions for puskesmas can optimize the suggestion box properly and pay attention to the patient waiting room, for further researchers to examine factors that affect patient satisfaction.